PEMBUATAN PROTOTYPE SISTEM PENGENDALI LAMPU RUMAH DENGAN PERANGKAT MOBILE ANDROID - Djuni H, I G. A. K. Diafari; Agung, I G A P Raka; Pramaita, N.; Sugiri, Made (Majalah Ilmiah Teknologi Elektro; Vol 14 No 2 (2015): (July - December) Majalah Ilmiah Teknologi Elektro, 2015)
AndroidisaLinux-basedoperatingsystemandis open source that can be developed independently so that more applications can be made. This application can also be integrated with other devices to control or control system is desirable. Media remote control or wireless (LAN) is a growing need for human behavior that want to move faster and farther range of location of residence. This research will be designed and built a prototype system controlling lights at home using Arduino microcontroller connected to mobile devices based on Android. Light control is done on a mobile device that is connected to the control system via WiFi Router lights. Wifi Router has sufficient coverage so that the owners of these devices can move more comfortably without having to control the lights via a switch on the wall of the house. The house lights controller circuit can adjust the lights ON and OFF as well as the Bright and Dim the lamp 1 and lamp 2. Lighting Control Application on mobile android devices already can set the lights on the control circuit.
Keywords: Android, mikrokontroler,kontrol lampu rumah,wifi